Building an Algorithm for Measuring C Programming Assignments Quality - Muhd Zulhafriz Aadel bin Marzuki, Muhd Zulhafriz (Universiti Teknologi PETRONAS, 2008)
The focuses of this final report is to provide a clear idea on the development of programming assignment’s quality measurement algorithm. The main content of the report is the discussion of the most possible methods used to measure programming assignments quality and how it is related to this project. The proposed algorithm was modified from an existing approach used to measure software quality known as the cyclomatic measure [6]. Modifications were based on observation, studies and data collected from lecturers who currently teaches programming courses in Universiti Teknologi Petronas (UTP). The tested programming language is C considering the problems in grading programming assignments are directly related with this subject in UTP.